INNOVATIVE MECHANISMS FOR IMPLEMENTING STATE ECONOMIC POLICY FOR POST-WAR RECONSTRUCTION OF UKRAINE: QUANTUM TRANSFORMATIONS AS A DRIVER OF DEVELOPMENT - Oleksiy Shkuratov; Liudmila Antonova; Roman Dzyuba (Публічне управління та регіональний розвиток)
The article emphasizes that quantum technologies are one of the key industries that can contribute to rapid economic growth and technological breakthrough. The quantum transformation of Ukraine's economy in the conditions of post-war recovery can become an important component of the state investment policy, which will stimulate innovative development and increase the country's competitiveness in the international arena. It is well-founded that its formation is one of the key trends in the development of the world's leading countries. Ukraine does not stand aside from global trends and strives for active integration into the world community, and therefore, for quantum transformation of the country. It is emphasized that quantum technologies have once already overturned the usual reality, giving us smartphones, ultra-flat TVs and, in general, all modern electronics. The second quantum revolution involves the introduction of quantum computers, quantum cryptography and quantum communication, capable of accelerating the development of new materials, optimizing logistics chains and increasing the level of data security. It is emphasized that the importance of these technologies is difficult to overestimate, as they become key elements in the struggle for technological superiority and have a significant impact on key economic processes. It was emphasized that the development of quantum technologies and implementation of quantum transformation require large-scale investments. Countries such as the USA, China, Great Britain, EU countries, etc. have already invested billions in the creation of super-powerful quantum computers, the development of quantum cryptography algorithms, and the scaling of quantum communication. It was emphasized that Ukraine needs serious efforts to meet the challenges and opportunities of the Second Quantum Revolution, as ignoring the quantum transformation will have serious consequences for the country's economy. It is justified that, exhausted by the full-scale invasion of Russian aggressors, Ukraine currently does not have the necessary financial resources for the development and introduction of quantum technologies. It has been proven that it is possible to improve the situation only if a balanced state investment policy for quantum transformation of the country is developed and implemented. A road map of the sequence of actions for the formation of the state policy on quantum transformation investment is proposed, the management of which will create a favourable environment for attracting investments and thereby accelerating the quantum transformation of the Ukrainian economy.